The effectiveness of a gender equality course in changing undergraduate midwifery students' attitudes towards domestic violence and gender roles - Emel Bahadir Yilmaz (University of Ostrava, 2018)
Aim: The aim of the study is to evaluate the effectiveness of a gender equality course in changing undergraduate midwifery students' attitudes towards domestic violence and gender roles. Design: A one-group before-after quasi-experimental design was used. Methods: First-year undergraduate midwifery students (n = 64) were pre- tested and post- tested for their attitude to domestic violence and gender roles using "The Attitudes Towards Domestic Violence Scale", and "The Gender Roles Attitudes Scale". Data were collected from a health science faculty in Giresun, Turkey. The pre- and post-test results were compared using a paired samples t-test. Results: While the mean score of the attitudes towards domestic violence was 55.23 ± 5.84 before the gender equality course, it increased to 57.71 ± 5.07 after the course. The increase in scores was statistically significant (p < 0.001). For attitudes to gender roles, the mean total score increased from 154.65 ± 14.16 to 164.72 ± 13.65 after the course (p < 0.001). Conclusion: The gender equality course helped students develop more positive attitudes towards domestic violence and gender roles. We achieved the aim of the study. We recommend that gender equality courses be integrated into the midwifery curriculum. Keywords: domestic violence, gender equality, gender roles, midwifery students.